Encouraging Bystanders to Promote Positive Parenting and Prevent Child Maltreatment in Retail Settings: Results of an Exploratory Qualitative Study. Issue 3 (16th March 2017) - Adhia, Avanti; Potter, Sharyn J.; Stapleton, Jane; Zuckerman, Barry; Phan, Nicole; Bair-Merritt, Megan
ABSTRACT: Community-level bystander approaches with media campaigns have successfully reduced sexual violence, but these programs have not been developed for child maltreatment prevention. This study informs the development of such programs in retail settings. Data were collected using focus groups with parents (n = 29) and surveys with child abuse experts (n = 10). Participants were asked how retail environments and employees could support parents during shopping excursions and what employees should do if they witnessed a concerning interaction. Participants highlighted (a) the need for in-depth training of employees to engage with parents and children to promote positive interactions and intervene in concerning situations; (b) the importance of the built environment (i.e., physical design and layout) to reduce stress and establish positive social norms through store-wide messaging; and (c) the role of parents in establishing expectations and actively including children in shopping. Future research should test approaches to training and engaging retail employees as supportive bystanders.